Corruption in the Procurement Process of Government Goods and Services - Riza, Wahyu Friyonanda; Alhadi, Muhammad Nurcholis; Lukman, Lukman; Ardiansyah, Ardiansyah; Suswadi, Suswadi (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
Procurement is one of the important functions of government organizations, one of which is channeling and distributing the state budget through the procurement of government goods/services. Procurement of government goods/services is a fundamental component of good governance. Government procurement of goods/services has the aim of, among other things, obtaining goods/services at prices that can be accounted for with appropriate quantity and quality and timely implementation. The implementation of procurement of goods and services in Indonesia until 2008 still used a conventional procurement system. In carrying out this tender, the interaction between the procurement committee and service providers is carried out directly so that there are many irregularities in the process of procuring goods and services. This type of research uses descriptive qualitative with analytical methods. The causes of irregularities in the procurement of goods and services in Indonesia include: a dominating bureaucratic leadership structure, lack of strong regulations on government procurement of goods/services, the system of government procurement of goods/services not working properly, employee salaries/incentives that are still low, the mental and moral of employees the low, the lack transparency, expensive political campaigns, the existence of political dynasties, big projects, crony interests, weakness order and law enforcement, weak legal profession.